PERAN ANTIHISTAMIN DALAM DERMATOLOGI: TINJAUAN FARMAKOLOGI, EFIKASI KLINIS, DAN KEAMANAN PADA KEHAMILAN - Yosserizal, Yosserizal; Anggi Syafitri Nasution; Arientina Amanda Filia; Vioni Yolisa Fitri; Muhammad Zaky; Abdullah, Dessy (Yayasan Nusantara Hasana Berdikari, 2025)
Antihistamines are widely used as first-line therapy for allergic skin disorders such as urticaria, dermatitis, and pruritus. Understanding their pharmacological mechanisms, classification, and safety profiles is essential for effective clinical application, particularly for long-term use and during pregnancy. This article is a narrative review based on scientific literature from national and international databases (PubMed, Scopus, SINTA), focusing on pharmacology, classification, clinical indications, contraindications, adverse effects, and safety of antihistamines in pregnancy. Antihistamines act as inverse agonists at histamine receptors, primarily H1 and H2. First-generation agents are lipophilic, crossing the blood–brain barrier and causing sedation, while second-generation antihistamines act selectively on peripheral receptors with fewer central nervous system side effects. During pregnancy, cetirizine and loratadine are recommended due to favorable safety profiles compared to first-generation drugs. In dermatology, antihistamines are effective in managing urticaria, angioedema, lichen simplex chronicus, mastocytosis, and various allergic skin conditions. The selection of antihistamines should be guided by pharmacokinetics, side effect profile, patient-specific conditions, and pregnancy safety. Second-generation antihistamines are generally preferred for long-term management owing to their efficacy and reduced central nervous system risk.